Glycemic Effects of Honey Compared to Glucose Using Standard OGTT - Naznin, Lubna; Hossain, Muhammad Rabiul; Saha, Debashish; Sultana, Sarmin; Sarkar, Mreenal Kanti (Journal of Enam Medical College, 2017)
Background: Honey, though rich in fructose and glucose, had been shown to have plasma glucose lowering effect. It may be as a result of insulin sensitization, enhanced insulin secretion and anti-oxidant activity. Objective: This study was designed to assess the glycemic effects of honey comparing to glucose. Materials and Methods: The study was carried out at Armed Forces Institute of Pathology (AFIP), Dhaka cantonment from September, 2015 to October, 2015 on 35 individuals who reported to AFIP for Oral Glucose Tolerance Test (OGTT). They were categorized to three groups based on OGTT ? Normal, Impaired glucose homeostasis (IGT or IFG), and Diabetes mellitus. On the subsequent day they were subjected to 52 mL honey load (equivalent to 75 gm by weight) to assess plasma glucose level after 1 hour and 2 hours posthoney load state. Student t-test was done to compare between means of plasma glucose level 1 hour after 75 gm glucose load and 1 hour after 75 gm honey load and also between means of plasma glucose level 2 hours after 75 gm glucose load and 2 hours after 75 gm honey load in the same individuals. Results: In all the three groups mean plasma glucose level in post-honey load state was found declined compared to post-glucose load state in both 1 hour and 2 hours specimens of HTT (Honey Tolerance Test) versus OGTT (Oral Glucose Tolerance Test) and this reduction was statistically significant (p<0.05). Conclusion: The study findings provide evidence that honey consumption causes less change in plasma glucose level than the equivalent quantity of oral glucose load regardless of status of glucose homeostasis. Further well designed researches are needed to determine the long term effects and beneficial quantity of honey, particularly in relation to diabetes mellitus. J Enam Med Col 2017; 7(2): 95-100